Type-Specific HPV Prevalence in Cervical Cancer and High-Grade Lesions in Latin America and the Caribbean: Systematic Review and Meta-Analysis - Ciapponi, Agustin (2011)
Fil: Ciapponi, Agustin. Institute for Clinical Effectiveness and Health Policy (IECS); Argentina.